In vivo lineage tracing in lymphopoiesis - Azenha, Sara Isabel Rodrigues (2021)
Lymphocytes are thought to differentiate from a common progenitor, which either remains in the bone marrow to generate B lymphocytes, or emigrates and, via blood, seeds the thymus to generate T lymphocytes. Such progenitors were originally termed common lymphoid progenitors (CLP), and a bone marrow population with both B and T lymphocyte potential was identified. Although CLP are clearly on their way to feed into the B lymphocyte lineage, their link to the T lymphocyte lineage in physiology is less clear. One concern is that CLP were never found in the thymus. Work from different labs have proposed several bone marrow progenitors as the true progenitors of T lymphocytes, but the identity of such cells remains elusive. Here, we sought to address this aspect by in vivo lineage tracing. For that purpose, we analyzed two mouse lines that expressed Cre recombinase from the interleukin 7 receptor alpha (IL7r) endogenous locus that differed in fluorescent reporter: IL-7riCre Rosa26-YFP and IL-7riCre Rosa26-tdTomato. In these mice, Cre expression follows the expression pattern of IL-7r, meaning that it will switch on the reporter to mark IL-7ra expressing cells, as well as all their progeny. With such tools in hand, we could determine progenitor-progeny relationships in the lymphocyte lineages. In addition, we used an inducible model, IL-7riCreERT2 Rosa26-tdTomato, to fine-tune those relationships at several timepoints after reporter induction. We identified a population that seems to be the bone marrow progenitor counterpart of the earliest thymic progenitor. This was validated in adoptive transfer experiments of purified cells into IL7r deficient recipients. Taken together, our data supports the notion that the CLP is a highly heterogeneous population, and we found a subpopulation within the CLP that is the bone marrow progenitor that originates the T lymphocyte lineage.